Community police role in maintaining security and supporting police institutions in the suburbs of Jerusalem Governorate - Zaatreh, Ina’am Eid; Lafy, Iyad Abdullah (Journal of Humanities & Social Sciences, 2021)
This study aims at examining the community police role in maintaining security in the suburbs of Jerusalem governorate. The study, used a descriptive exploratory approach. A questionnaire was designed and distributed to the study sample of (52) employees working in government institutions in the suburbs of Jerusalem, after verifying its validity and stability. its final form consisted of (37) paragraphs distributed over five axes. The study’s most important results were: The police community ability to promote faith and loyalty got the highest arithmetic averages of (73.3), followed by their ability to maintain peace in community which got an arithmetic averages of (72.1). Finally their success factors got an arithmetic averages of (71.2). The study recommended the following: Establishing mobile offices for the community police. The inclusion of crime prevention in the education curriculum, that should be taught by police officers. Creation of Civil Peace units in the Palestinian governorates, and to headed by graduates of law or Social Science.